Least developed countries and the Multidimensional Poverty Index (MPI) - Alkire, S; Robles Aguilar, G (Oxford Poverty & Human Development Initiative (OPHI), 2012)
In 2011, the Multidimensional Poverty Index (MPI) was released for 109 countries. Of these, 39 countries are identified as ‘least developed countries’ (LDCs). This note provides briefing facts regarding MPI in these countries.